Pemanfaatan Kulit Durian Sebagai Pengganti Sebagian Semen Dalam Pembuatan Beton K-300 - Fynnisa Z; Muhammad Irwansyah; Putri Handayani (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2022)
Concrete is one of the most widely used materials in the construction industry. The constituent materials of concrete are materials that are widely found in nature, including sand and gravel and cement. Therefore, the availability of these natural materials is increasingly running low. While there are many wastes that are not used optimally, one of them is durian skin. The purpose of this study was to determine the results of testing the compressive strength of concrete with the addition of durian skin by 3%, 6%, and 9%. The planned concrete quality is 24 MPa with an estimated age of 28 days. This study used a cylindrical specimen with a size of (15x30) cm, and the specimens made in this study were 4 specimens consisting of 3 variations. The conclusion of this study is that the greater the percentage of the mixture for durian peel as an added ingredient in reducing cement, the higher the compressive strength produced.